Construction of Long‐Wavelength Fluorescein Analogues and Their Application as Fluorescent Probes. Issue 21 (15th April 2013) - Xiong, Xiaoqing; Song, Fengling; Chen, Gengwen; Sun, Wen; Wang, Jingyun; Gao, Pan; Zhang, Yukang; Qiao, Bo; Li, Wenfang; Sun, Shiguo; Fan, Jiangli; Peng, Xiaojun
<x xml:space="preserve">Abstract</x> Born to dye: Five fluorescein analogues were synthesised (see scheme). One analogue was found to emit in the NIR region with a high quantum yield, excellent photostability and good permeability. Three derivatives were found to specifically stain mitochondria and one dye responds to thiols with a strong turn‐on NIR fluorescence signal and colorimetric change, in vitro and in vivo.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>